HISTOLOGICAL OUTCOME OF DUODENAL BIOPSIES IN PATIENTS WITH CLINICALLY SUSPECTED CELIAC DISEASE - A STUDY OF 100 CASES: Duodenal Biopsies in Celiac Disease - Sarfraz, Dr Tariq; Matloob Ur Rehman, Muhammad; Tariq, Hina; Khan, Saleem Ahmed; Tariq, Humaira; Waqar, Samina; Sadia, Aiza; Kanwal, Motia; Zafar, Faryal; Hanif, Amna (Pakistan Armed Forces Medical Journal, 2018)
Objective: To see the histological outcome of duodenal biopsies done in patients clinically suspected of celiac disease. Study Design: Prospective descriptive study. Place and Duration of Study: Histopathology Department, Army Medical College Rawalpindi, from 1 Jan 2017 to 30 Jun 2017. Material and Methods: One hundred (100) cases were included in the study. Duodenal biopsies done in patients clinically suspected of celiac disease were included in the study. Inadequate biopsies were excluded from the study. All the normal and abnormal histological features were noted to make the diagnosis. Data was entered and analyzed by using SPSS version 17. Results: Duodenal biopsies of 100 patients, done in clinically suspected cases of celiac disease were analyzed histologically. Out of these 100 cases, 46 cases (46%) showed histological features consistent with celiac disease, while 38 cases (38%) revealed chronic non specific duodenitis, 2 cases (2%) were of giardiasis, while 14 biopsies (14%) were unremarkable with no significant pathology. Conclusion: A significant number of cases clinically suspected of celiac disease may not be showing histological features consistent with celiac disease on duodenal biopsies. Due to the changing presentation of disease, as well as the recognition of a number of potential clinical and histopathological mimics, communication between pathologists and gastroenterologists is essential for appropriate interpretation of duodenal biopsy specimens.